Characterization of mechanical properties of hybrid contrast agents by combining atomic force microscopy with acoustic/optic assessments. Issue 3 (8th February 2016) - Guo, Gepu; Tu, Juan; Guo, Xiasheng; Huang, Pintong; Wu, Junru; Zhang, Dong
Abstract: Multi-parameter fitting algorithms, which are currently used for the characterization of coated-bubbles, inevitably introduce uncertainty into the results. Therefore, a better technique that can accurately determine the microbubbles׳ mechanical properties is urgently needed. A comprehensive technology combining atomic force microscopy, optical, and acoustic measurements with simulations of coated-bubble dynamics was developed. Using this technique, the mechanical parameters (size distribution, shell thickness, elasticity, and viscosity) of hybrid (ultrasound/magnetic-resonance-imaging) contrast microbubbles and their structure–property relationship were determined. The measurements indicate that when more superparamagnetic iron oxide nanoparticles are embedded in the microbubbles׳ shells, their mean diameter and effective viscosity increase, and their elastic modulus decreases. This reduces the microbubbles׳ resonance frequency and thus enhances acoustic scattering and attenuation effects.